If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + 8) = 8x + 62 Reorder the terms: 9(8 + x) = 8x + 62 (8 * 9 + x * 9) = 8x + 62 (72 + 9x) = 8x + 62 Reorder the terms: 72 + 9x = 62 + 8x Solving 72 + 9x = 62 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 72 + 9x + -8x = 62 + 8x + -8x Combine like terms: 9x + -8x = 1x 72 + 1x = 62 + 8x + -8x Combine like terms: 8x + -8x = 0 72 + 1x = 62 + 0 72 + 1x = 62 Add '-72' to each side of the equation. 72 + -72 + 1x = 62 + -72 Combine like terms: 72 + -72 = 0 0 + 1x = 62 + -72 1x = 62 + -72 Combine like terms: 62 + -72 = -10 1x = -10 Divide each side by '1'. x = -10 Simplifying x = -10
| 4.5x=270 | | x-6(-4)=-26 | | 6x=18(x^1/2) | | 2y^2+7y-81=0 | | log(52x)=67 | | 3x-2+2x+7=9 | | 1.4x+3y=21 | | -(17+9m)=82 | | (4/5)z=20 | | 15.18=.5x+3.68 | | 12n+-2=46 | | 0=-2x^2+23x+39 | | 3x+9=1x | | Y-4.9=50 | | 8p+2=18 | | -24+1+x=-3+13 | | 3(2x-2)=-18 | | 111=4x-5 | | 5/6x=20;x= | | 0.2x+6=0.5x+18 | | 12=3.1x-59.3 | | 3s+9=24 | | (a-2b)-(a-b)= | | 100.78=.14x+2.78 | | Ydx+(x+2y)=0 | | 7(x-5)=8+7x | | -5+18x=-77 | | 7-6(-2x-10)=199 | | -1(x+3)=-11 | | 0.18x+4=-0.2x+4.76 | | (x^2-12.75)/(x-5)-2x=0 | | y=160(120)+700 |